Decline in prevalence and asymmetric distribution of human T cell lymphotropic virus 1 and 2 in blood donors, State of Minas Gerais, Brazil, 1993 to 2007 Declínio na prevalência e distribuição assimétrica do vírus linfotrópico de células T humanas em doadores de sangue, Estado de Minas Gerais, Brasil, 1993 a 2007 - Maria Regina Dias-Bastos; Cláudia Di Lorenzo Oliveira; Anna Bárbara de Freitas Carneiro-Proietti (Revista da Sociedade Brasileira de Medicina Tropical, 2010)
INTRODUCTION: Human T cell lymphotropic virus types 1 and 2 (HTLV-1/2) are endemic in Brazil and are screened for in transfusion services since 1993. This study evaluated the evolution of the prevalence of HTLV-1 and 2 in blood donors of the Hemominas Foundation from 1993 to 2007, and its geographical distribution in State of Minas Gerais, Brazil. METHODS: The Hemominas Foundation is a centralized blood center in Minas Gerais, Brazil. The sources of data were the Hemominas Foundation Technical Bulletin and files from the centralized serological laboratory. Donors were tested in the period using enzyme linked immuno sorbent assays (ELISA), followed by Western blot, when repeatedly reactive. The data were analyzed by EPIINFO 6.2 and TABWIN 3.5 softwares. RESULTS: The average seroprevalence in the period 1993-2007 was 0.1%. A steady decline occurred from 0.4% in 1993 to below 0.1% in 2002 and later, with a transient peak of 0.5% in 1994. HTLV reactivity distribution was asymmetrical in the state, with regions of higher prevalence, interspersed with low prevalence areas. Comparison of positive and negative donors verified that increasing age was proportional to virus positivity. Odds ratio for age ranged from 1.43 (30 to 39 years-old) to 3.09 (50 to 65 years-old). Women had a greater chance of being positive (OR-1.64), as previously described. CONCLUSIONS: Possible explanations for HTLV-1/2 prevalence decline are the exclusion of positive donors from the donor pool, an increase in repeat donors and ELISA test improvement, with reduction in the number of false positive results. INTRODUÇÃO: Os vírus linfotrópicos de células T humanas 1 e 2 (HTLV-1/2) são endêmicos no Brasil e são testados nos serviços de transfusão desde 1993. Este estudo avaliou a evolução da prevalência do HTLV-1 e 2 em doadores de sangue da Hemominas, de 1993 a 2007, bem como sua distribuição geográfica no Estado de Minas Gerais, Brasil. MÉTODOS: A Hemominas é um serviço transfusional centralizado em Minas Gerais, Brasil. As fontes de dados foram o Boletim Técnico da Fundação Hemominas, e os dados informatizados do laboratório central de sorologia. Os doadores foram testados no período utilizando ensaio enzimático (ELISA), seguido de Western blot, para confirmação, se repetidamente reagentes. Os dados foram analisados utilizando EPIINFO 6.2 e TABWIN 3.5. RESULTADOS: A prevalência media no período 1993-2007 foi de 0,1%. Houve declínio contínuo de 0,4% em 1993 para menos de 0,1% de 2002 em diante, com um pico transitório de 0,5% em 1994. A distribuição do HTLV foi assimétrica, com alternância de regiões de alta e baixa prevalências. A comparação entre doadores positivos e negativos mostrou que a idade aumenta a positividade para o vírus. A OR para idade variou de 1,43 (30 a 39 anos) a 3,09 (50 a 65 anos). As mulheres tiveram chance maior de ser positivas (OR-1,64), como descrito anteriormente. CONCLUSÕES: As possíveis explicações para o declínio do HTLV-1/2 foram a exclusão de doadores positivos, aumento nos doadores de repetição, e melhora nos testes de ELISA, com redução do número de testes falso positivos.